Distribution, Diversity and Roles of CRISPR-Cas Systems in Human and Animal Pathogenic Streptococci - Lemaire, Coralie; Le Gallou, Brice; Lanotte, Philippe; Mereghetti, Laurent; Pastuszka, Adeline (Frontiers in Microbiology, 2022)
Streptococci form a wide group of bacteria and are involved in both human and animal pathologies. Among pathogenic isolates, differences have been highlighted especially concerning their adaptation and virulence profiles. CRISPR-Cas systems have been identified in bacteria and many streptococci harbor one or more systems, particularly subtypes I-C, II-A, and III-A. Since the demonstration that CRISPR-Cas act as an adaptive immune system in Streptococcus thermophilus, a lactic bacteria, the diversity and role of CRISPR-Cas were extended to many germs and functions were enlarged. Among those, the genome editing tool based on the properties of Cas endonucleases is used worldwide, and the recent attribution of the Nobel Prize illustrates the importance of this tool in the scientific world. Another application is CRISPR loci analysis, which allows to easily characterize isolates in order to understand the interactions of bacteria with their environment and visualize species evolution. In this review, we focused on the distribution, diversity and roles of CRISPR-Cas systems in the main pathogenic streptococci.